Rancang Bangun Sistem Keamanan Benda Pajangan dengan Notifikasi Telegram - A. A. Jaya Kesuma Wardana; I Gede Santi Astawa; I Putu Satwika (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
This paper presents a security monitoring system designed for high-value museum and gallery display items such as statues, paintings, and pottery, which are susceptible to theft due to their aesthetic, historical, and economic worth. The design integrates an ESP32 microcontroller with an HC-SR04 ultrasonic sensor to detect object movement or removal. Upon detecting unauthorised movement or disappearance, the system dispatches a real-time notification via the Telegram application to alert the user. This study consists of problem identification, literature review, system architecture design, prototype implementation, and thorough testing. Experimental results demonstrate the system’s effectiveness in detecting object displacements and absences, with notification latency under two seconds and successful message delivery across all test scenarios. These findings demonstrate a practical security measure for art and historical collections